LITERATURE AND HISTORICAL-SOCIAL REPRESENTATION IN NOVEL FILHOS DO DESTINO BY HERNANI DONATO - Pinto, Jesuino Arvelino (Fundacao Univ Tocantins, 2018)
In the set of novels by Hernani Donato, one can see the predominance of narratives that trace the path of the man circumscribed to a space that makes him attached to the social landscape and submitted to laws that cancel his dreams, utopias and freedom, preventing him from being realized in his fullness. Such is the content of Filhos do Destino, Donato's first novel, which fulfills the function of presenting the writer to the literary scene, its subtitle is History of Coffee and Immigrant in Sao Paulo. The proposal of this work is to reveal the narrative strategies used by Donato in his elaboration from theoretical discussions about narrative voices and the modern novel, focusing on temporal and spatial issues and the subjectivity of the author's repertoire, evidencing aspects of originality, which, from the reconstruction and reformulation of historical episodes and the daily life, give rise to a new novel.
Keywords: Social Romance; Hernani Donato; Filhos do Destino